Latihan Dasar Kepemimpinan Dalam Membentuk Jiwa Kepemimpinan Pengurus Fakultas Ilmu Sosial Dan Ilmu Politik - Riski Hidayat; Ikromi Aliftian Cahya; Aos Kuswandi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Leadership is a competency that must be possessed by a person. Leadership is not only needed in organizing but in the smallest thing, namely leading oneself to achieve life goals, a leadership spirit is needed from the individual. One of the goals of the faculty is to prepare students to have a leadership spirit, especially the SEMA FISIP administrators who also play an important role in running campus organizations. Basic student leadership training is one of the faculty's efforts to develop student leadership. The purpose of writing this scientific paper is to find out what students receive in basic student leadership training and how the knowledge from this activity impacts participants, the faculty and the campus. This study uses a qualitative research method with data collection techniques through observation and interviews. Based on the results of the study, LDKM activities at the FISIP faculty, Universitas Islam 45 Bekasi are activities that aim to prepare members of the organization to have a leadership spirit so that they are able to carry out their duties as SEMA FISIP administrators and can be an example for other students. Participants are equipped with knowledge about leadership character, discipline, how to organize, national values and love for the environment. Through this activity, the knowledge received becomes the provision for participants to develop a leadership spirit in carrying out their duties as SENAT administrators and has a positive impact on the faculty by providing an example for other students.